Who are happy survivors? Physical, psychosocial, and spiritual factors associated with happiness of breast cancer survivors during the transition from cancer patient to survivor. Issue 11 (20th March 2017) - Kang, Danbee; Kim, Im‐Ryung; Choi, Eun‐Kyung; Yoon, Jung Hee; Lee, Se‐Kyung; Lee, Jeong Eon; Nam, Seok Jin; Han, Wonshik; Noh, Dong‐Young; Cho, Juhee
Abstract: Objective: This study aims to evaluate physical, psychosocial, and spiritual factors associated with happiness in breast cancer survivors during the reentry period. Methods: It is a cross‐sectional study with 283 nonmetastatic breast cancer survivors who completed treatment within 1 year. We included survivors who completed questionnaires on happiness and health‐related quality of life (QoL) 2 years after cancer diagnosis. Happiness and QoL was measured using the Subjective Happiness Scale and EORTC QLQ‐C30, respectively. Multivariable logistic regression was used to find factors associated with happiness. Results: The mean age of the study participants was 48.5 ± 7.8 years. Among the 283 survivors, 14.5%, 43.8%, 32.5%, and 2.1% reported being "very happy, " "happy, " "neutral, " and "not happy at all, " respectively. Happy survivors reported a better general health status and QoL (67.6 vs 49.6; P  < .01), and fewer symptoms compared to unhappy survivors. Happy survivors were more likely to feel certain about the future (27.2% vs 11.9%, P  < .01), have a strong purpose in life (22.4% vs 9.3%, P  < .01), and feel hopeful (36.4% vs 8.5%, P  < .01) compared to unhappy survivors. In a multivariate model, having purpose (OR = 2.50, 95% CI 1.42‐4.40) and hope (OR = 4.07, 95% CI 2.23‐7.45) in life were found to be associated with happiness. Conclusions: During the reentry period, breast cancer survivors who are hopeful and have a clear purpose in life are more likely to be happy than those who are not. Setting proper life goals might be beneficial to help breast cancer survivors who experience persistent QoL issues.